POTENSI PENGEMBANGAN PASAR TEMATIK DI KOTA SEMARANG - Margunani Margunani; Sucihatiningsih Dian Wisika Prajanti; Asrori Asrori; Yozi Aulia Rahman; Nurjannah Rahayu Kistanti (Jurnal Riptek, 2018)
To maintain the existence of traditional markets, one of the efforts that can be done is to make traditional markets become thematic markets. The purpose of this study is to identify the potential development of thematic markets in Semarang City and to find out the thematic market development strategies in Semarang City. This research method is secondary data and primary data. Determination of samples in this study was carried out by purposive sampling method, that is judgment sampling. The analytical method uses description analysis, and SWOT analysis. The results of the study show that the potential of thematic market development in Semarang City is directed at two things, (a) thematic-based products, (b) themati-based village (c) based on creative economy. The potential of thematic / tourism village based thematic market development is directed at thematic villages that have been formed and developed by each Subdistrict according to their characteristics, potential and superiority. Some thematic market development strategies based on SWOT Analysis are facilitation of funds and bureaucracy in the development of thematic markets, conducting marketing promotions on thematic markets on a regular basis to the community, and empowering the market community. Efforts should be made to integrate tourism villages, thematic products, industrial centers and people's markets in maximizing the development of thematic markets in the city of Semarang so that there is no need to build new thematic markets that spend a lot of budget.